Analisis Pengaruh Ketersediaan Produk Harga dan Lokasi Terhadap Keputusan Pembelian Sepeda Motor di Dealer Honda Krida Motor - Aswan Aswan; Muhajirin Muhajirin; Nur Khusnul Hamidah (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
The aim of this research is to find out whether there is a simultaneous influence of product availability, price and location on the decision to purchase a motorbike at the Krida Motor dealer. This type of research includes associative research, which is a method carried out to determine the relationship between two or more variables, namely variables (X) and (Y). The population in this study were all people in the city of Bima who had purchased at the Bima Honda Krida Motor Dealer. According to calculations using the Unknown Population formula, a sample of 96.04 was obtained and rounded to 96 respondents. Data analysis involved validity and reliability, classical assumption test, multiple linear regression, multiple correlation test, multiple determination test, as well as the T test and F test. The results of the research show that there is no partial influence of product availability on the decision to purchase a motorbike at the Krida Motor Dealer. There is a partial influence of price on the decision to purchase a motorbike at the Krida Motor dealer. There is a partial influence of location on the decision to purchase a motorbike at the Krida Motor dealer. There is a simultaneous influence of product availability, price and location on the decision to purchase a motorbike at the Krida Motor dealer.